Cord Blood Serum Composition After Low-Temperature Storage at –40°C - Salnykov, Dmytro; Gorina, Olga; Prokopiuk, Olga; Mykhalchuk, Tetyana; Shevchenko, Mariia (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):303